2022
DOI: 10.1021/acsaelm.2c00054
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Electrical Performance and Bias Stability of RF-Sputtered Indium Tin Zinc Oxide Thin-Film Transistors with Vertical Stoichiometric Oxygen Control

Abstract: Indium tin zinc oxide (ITZO) thin-film transistors (TFTs) with different channel structures are investigated. The electrical performance and bias stress stability of bilayer-channel ITZO TFTs are enhanced in comparison with those of single-channel ITZO TFTs. The bilayer channel consists of an oxygen-uncompensated channel layer and an oxygen-compensated capping layer, while the single channel is an oxygen-uncompensated channel layer. The electrical properties of the bilayer-channel films are fine-tuned by adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…This is due to additional oxygen CCL layer in device B, which can effectively prevent the oxygen absorption. [ 18 ] We analyzed the NBS and PBS results further by fitting the stress time dependence of ∆ V TH with the following stretched‐exponential equation [ 25 ] ΔVTHbadbreak=ΔVTH0{1badbreak−exp[badbreak−false(t/τfalse)β]}\[ \begin{array}{*{20}{c}}{\Delta {V_{{\rm{TH}}}} = \Delta {V_{{\rm{TH0}}}}\left\{ {1 - \exp \left[ { - {{(t/\tau )}^\beta }} \right]} \right\}}\end{array} \] where ∆ V TH0 is the ∆ V TH at infinite stressing time, τ is the characteristic trapping time, and β is the stretched‐exponential exponent. The stress time dependence of ∆ V TH for both NBS and PBS is well fitted with Equation () as shown in Figure S3 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is due to additional oxygen CCL layer in device B, which can effectively prevent the oxygen absorption. [ 18 ] We analyzed the NBS and PBS results further by fitting the stress time dependence of ∆ V TH with the following stretched‐exponential equation [ 25 ] ΔVTHbadbreak=ΔVTH0{1badbreak−exp[badbreak−false(t/τfalse)β]}\[ \begin{array}{*{20}{c}}{\Delta {V_{{\rm{TH}}}} = \Delta {V_{{\rm{TH0}}}}\left\{ {1 - \exp \left[ { - {{(t/\tau )}^\beta }} \right]} \right\}}\end{array} \] where ∆ V TH0 is the ∆ V TH at infinite stressing time, τ is the characteristic trapping time, and β is the stretched‐exponential exponent. The stress time dependence of ∆ V TH for both NBS and PBS is well fitted with Equation () as shown in Figure S3 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…This is due to additional oxygen CCL layer in device B, which can effectively prevent the oxygen absorption. [18] We analyzed the NBS and PBS results further by fitting the stress time dependence of ∆V TH with the following stretched-exponential equation [25] τ { }…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, amorphous silicon (a-Si) and low-temperature polycrystalline silicon (LTPS) TFTs have been used as a backplane of the flat-panel X-ray detector; however, the low carrier mobility of a-Si , and poor X-ray radiation tolerance of LTPS channel materials ascribed to the degraded crystalline structure induced by X-ray irradiation make them not suitable for the channel material of highly stable TFTs for the X-ray detector applications. Recently, oxide semiconductor TFTs have been of particular interest as promising candidates for the TFT panels of X-ray detectors owing to their excellent electrical characteristics such as high carrier mobility, low leakage current, and high on–off current ratio. However, considering the degraded reliability of oxide semiconductor TFTs under light illumination stress, it is necessary to investigate the effects of high energy X-ray radiation on the electrical performance of oxide semiconductor TFTs to verify their practical use under radiation-harsh environments. A few studies have reported the electrical characteristics of the oxide semiconductor TFTs such as amorphous In–Ga–Zn–O (a-IGZO) TFTs under X-ray irradiation or UV/visible light radiation, exhibiting the shifts of threshold voltage ( V TH ); , however, little effort has been made to improve the radiation hardness of the oxide semiconductor TFTs under high energy X-ray irradiation and investigate the mechanisms of radiation damage to the oxide semiconductor TFT in detail.…”
Section: Introductionmentioning
confidence: 99%